ОПТИМІЗАЦІЯ КОМПЛЕКСНОГО ЛІКУВАННЯ ІЗ ЗАСТОСУВАННЯМ ПРЕФОРМОВАНИХ ФАКТОРІВ У ЖІНОК У ПОСТМЕНОПАУЗАЛЬНОМУ ПЕРІОДІ, ХВОРИХ НА ОСТЕОАРТРОЗ КОЛІННИХ СУГЛОБІВ (World Science, 2019)
The article presents the issues of complex treatment of osteoarthritis of the knee with the use of preformed factors in postmenopausal women compared to standard drug therapy. The study included 60 women aged 50 to 75 years with clinical manifestations of osteoarthritis of the knee joints in the postmenopausal period. Complex treatment with preformed factors has been found to be an effective treatment for this category of patients, improving the clinical course of osteoarthritis by 53% and improving quality of life.